Answer:
Part (A) The wrong step is step 3
Part (B) The correct option is D) x ≥ −1/3
Explanation:
Consider the provided inequality.
![4-6x\geq -15x+1](https://img.qammunity.org/2020/formulas/mathematics/high-school/2fgjjfjwprr8nusdpfyzt2z2p5cey2f7mg.png)
Step 1. subtract 1 from both the sides.
![4-1-6x\geq -15x+1-1](https://img.qammunity.org/2020/formulas/mathematics/high-school/ogd4wnhgt5exzrcxvzcfx2q0kts5eabuxf.png)
![3-6x\geq -15x](https://img.qammunity.org/2020/formulas/mathematics/high-school/5y0gwxaakystnamh46z2v56kc6mbqtaj4g.png)
Step 2. Add 6x both sides.
![3-6x+6x\geq -15x+6x](https://img.qammunity.org/2020/formulas/mathematics/high-school/1po7wvp3wgx2ylcuk99p8jx0gq0tmc2232.png)
![3\geq -9x](https://img.qammunity.org/2020/formulas/mathematics/high-school/wtnzhuza7wbwy5i8bp3mzzbu6bgybyncy3.png)
Step 3. Divide both sides by -9 and change the sign of inequality.
![(3)/(-9)\leq (-9x)/(-9)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nsl9mpdruibh4ovh9r16jog221wdjshvai.png)
![(-1)/(3)\leq x](https://img.qammunity.org/2020/formulas/mathematics/high-school/ukdw6le3fa2q3zevl3d12sclceztkr6b4j.png)
Part (A) The wrong step is step 3
Part (B)
From the above calculation the solution of the inequality is
![(-1)/(3)\leq x](https://img.qammunity.org/2020/formulas/mathematics/high-school/ukdw6le3fa2q3zevl3d12sclceztkr6b4j.png)
Hence, the correct option is D) x ≥ −1/3